2006
DOI: 10.1016/s0210-4806(06)73526-4
|View full text |Cite
|
Sign up to set email alerts
|

Evidencia de transmisión autosómica dominante a través de la línea materna en un caso de discinesia ciliar primaria

Abstract: An atypical case of primary ciliary dyskinesia is presented in which the inheritance, rather than the classical autosomal recessive, appears to be transmitted as an autosomal dominant trait through the maternal line. The case involves two brothers of 29 and 30 years of age, married without children, with a history of infertility, frequent episodes of sinusitis, and recurrent pulmonary infections. Their mother and sister have chronic bronchopathy of unknown etiology. Their father is healthy without pulmonary pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Primary ciliary dyskinesia (PCD; MIM #244400) is a genetically heterogeneous ciliopathy inherited in an autosomal-recessive fashion [Bush et al, 2007 ], although there have been a few instances where PCD has been reported to follow an autosomal-dominant inheritance pattern [Narayan et al, 1994 ; Alvarez Gonzalez et al, 2006 ]. PCD is a rare (∼one in 20,000) disorder associated with abnormal (respiratory) ciliary structure and/or function, abnormal sperm motility (and therefore infertility or later subfertility), and/or situs abnormalities [Zariwala et al, 1993 ].…”
mentioning
confidence: 99%
“…Primary ciliary dyskinesia (PCD; MIM #244400) is a genetically heterogeneous ciliopathy inherited in an autosomal-recessive fashion [Bush et al, 2007 ], although there have been a few instances where PCD has been reported to follow an autosomal-dominant inheritance pattern [Narayan et al, 1994 ; Alvarez Gonzalez et al, 2006 ]. PCD is a rare (∼one in 20,000) disorder associated with abnormal (respiratory) ciliary structure and/or function, abnormal sperm motility (and therefore infertility or later subfertility), and/or situs abnormalities [Zariwala et al, 1993 ].…”
mentioning
confidence: 99%